High Sensitive C-Reactive Protein(HsCRP): A Simplistic Biomarker of Stroke Severity - Onjal Taywade (Walawalkar International Medical Journal, 2020)
Background and Introduction: Stroke has become an important cause of death as well as disability across the globe. Though the diagnosis of stroke is based on clinical evaluation and imaging, there is need to find biomarkers that can aid in diagnosis,prognosis and overall management of stroke.